Analisis Pengembangan Sumber Daya Manusia Melalui Pelatihan Untuk Meningkatkan Kinerja di PT. Gapura Angkasa Bandara Udara Sentani Jayapura - Caritas Yubelia S M Rahawarin; Walid Jumlad (Jurnal Multidisiplin Madani, 2022)
The growing world of aviation certainly has implications for human resources and is an asset that must be developed in order to be able to face the developments and challenges faced by the company. Every company certainly has HR management to improve the performance of its employees. For example, research that has been carried out on 27 September-17 October 2021 by directly interviewing 6 resource persons. Where 4 people are the main informants. Descriptive qualitative method as a way of collecting data. The research aims to find out how HR development through training to improve employee performance, find out what are the obstacles in HR management in development through training to improve employee performance, and know HR development strategies through training to improve employee performance at PT. Gapura Angkasa, Jayapura Sentani Airport. PT. Gapura Angkasa of Sentani Jayapura Airport is general and comprehensive for all employees to create multitasking human resources. In addition, there is further training for licensed employees. Training is usually done in person, but during a pandemic the training is carried out online. The training received by employees is not limited to training at PT Gapura Angkasa, but employees also receive training from airlines handled by PT Gapura Angkasa so that employee performance can be maximized in accordance with existing SOP. Non-licensed training is carried out every 3 to 6 months, while licensed training is carried out periodically every 1 or 2 years according to the validity period of the license. The company's management makes a strategy in training in such a way that the performance of its employees is maximized, effective, efficient, and in accordance with applicable SOPs. Based on the performance indicators, the performance of the HR at PT Gapura Angkasa is in accordance with the indicators.